(untitled) (Research, Society and Development, 2022)
Quantitative documentary aimed to analyze clinical outcomes and sociodemographic and clinical characteristics of elderly hospitalized by Coronavirus (COVID-19). Documental research was realized, with data from Hospital Epidemiology Center on elderly people hospitalized with COVID-19 in 2020. The results show male predominated (50.3%), mean age of 71.9, and multimorbidities (88.8%). In the prognosis, 70.9% were discharged 22.9% died and 6.1% were transferred to other hospitals. At discharges prevailed: mean age of 70.4; male 53.3%, used oxygen support (72.44%), in which 5.5% used mechanical ventilation, were prone (79.53%), had a mean partial pressure of oxygen (PaO2) by 102.79 ± 47.47, D-Dimer of 2016.98 ± 1994.94, and the Computed Tomography (CT) scan with aspect in opacities occurred in 66.79%. In deaths, predominated: mean age of 76.6, female (58.5%), need oxygen therapy in 97.53% of the elderly, use of mechanical ventilation (MV) 58.54% and prone position in 60.98%, mean D-Dimer of 5022.29, Computed Tomography (CT) scan with aspect in opacities in 73.2%. Finally, in discharge and death outcomes the prevalent morbidities: SAH, diabetes Mellitus and cardiovascular disease. The mean age was 70.4 (discharge) and 76.7% (death), 97.53% used oxygen, and 58.54% required intubation.